EMOTION WORD FLUENCY TEST DITINJAU DARI PENGALAMAN EMOSIONAL DALAM PEKERJAAN: EMOTION WORD FLUENCY TEST VIEWED FROM EMOTIONAL EXPERIENCE AT WORK - Heni Gerda Pesau (Jurnal Psikologi Jambi, 2023)
ABSTRACT Introduction This study aimed to analyze the performance of participants in the Emotion Word Fluency Test (EWFT) through scores generated from emotional experiences at work. Fire fighters as one type of work that has risk of accidents that can trigger individual emotional experiences. Method 90 participants were involved aged 18 – 53 years who were divided into two groups of participants (Firefighter group = 60; Staff group = 30). The EWFT scores were analyzed using the Mann Whitney Test. The results showed that the two groups showed a significant difference in EWFT scores between the two groups on the number of correct words and negative emotion words, that the rank of the firefighter group was lower than the staff group. Conclusions The subjective experience of participants in work can be a factor that plays a role in producing emotional words. Participants' understanding of the test instructions given also needs to be considered in scoring system. Keywords : Emotional Word Fluency test, emotional experiences, producing emotional words. ABSTRAKPendahuluan Penelitian ini bertujuan menganalisis performansi responden dalam emotion word fluency test (EWFT) melalui skor yang dihasilkan ditinjau dari pengalaman emosional yang dialami dalam pekerjaan. Pemadam kebakaran sebagai salah satu jenis pekerjaan yang memiliki resiko terpapar kejadian yang dapat memicu pengalaman emosional individu. Metode Partisipan yang dilibatkan sebanyak 90 orang berusia 18 – 53 tahun yang terbagi dalam dua kelompok partisipan (kelompok pemadam kebakaran = 60 orang; Kelompok staf = 30 orang). Skor EWFT dianalisis menggunakan Mann Whitney Test. Hasil Uji hipotesis menunjukkan kedua kelompok menunjukkan perbedaan skor EWFT yang signifikan antara kedua kelompok pada jumlah kata yang benar dan kata emosi negatif, yang mana peringkat rerata kelompok pemadam kebakaran lebih rendah daripada kelompok staf. Kesimpulan Pengalaman subjektif partisipan dalam pekerjaan dapat dikaitkan sebagai faktor yang berperan dalam menghasilkan kata emosi. Pemahaman partisipan terhadap instruksi tes yang diberikan juga perlu dipertimbangkan dalam melakukan perhitungan skor. Kata Kunci : Emotion Word Fluency Test, pengalaman emosional, menghasilkan kata emosi